2011
DOI: 10.4103/0973-1482.82914
|View full text |Cite
|
Sign up to set email alerts
|

Computerized tomography-guided percutaneous high-dose-rate interstitial brachytherapy for malignant lung lesions

Abstract: CT-guided HDRIBT is a safe and feasible non-surgical treatment option for patients with MLL. It provides effective tumor control and needs to be studied further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 19 publications
(41 reference statements)
1
8
0
Order By: Relevance
“…Computed tomography (CT-guided) minimally invasive Iridium-192 high-dose-rate (HDR) brachytherapy (BRT) has been introduced as a form of local radiation treatment for inoperable primary and metastatic lung cancer [ 1 , 2 ]. CT-HDRBRT is performed mostly through collaboration with interventional radiologists for insertion of brachytherapy catheters into the tumor [ 3 ].…”
Section: Purposementioning
confidence: 99%
“…Computed tomography (CT-guided) minimally invasive Iridium-192 high-dose-rate (HDR) brachytherapy (BRT) has been introduced as a form of local radiation treatment for inoperable primary and metastatic lung cancer [ 1 , 2 ]. CT-HDRBRT is performed mostly through collaboration with interventional radiologists for insertion of brachytherapy catheters into the tumor [ 3 ].…”
Section: Purposementioning
confidence: 99%
“…50 In group A, postoperative bloody sputum was worse than that in preoperation in 1 patient. The CT scan also confirmed the bleeding inside the pulmonary lesions.…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies had found that the incidence of bloody sputum after seed implantation was 0% to 20%. 50 In group A, postoperative bloody sputum was worse than that in preoperation in 1 patient. The CT scan also confirmed the bleeding inside the pulmonary lesions.…”
Section: Discussionmentioning
confidence: 86%
“…For HDR interstitial brachytherapy of lung lesions, the use of a single brachytherapy catheter in tumors up to a 4 cm diameter, has been previously reported [28,29]. The use of a single catheter showed a 0% complication rate of pneumothorax and a 75% tumor control rate for 20 Gy of prescribed dose in a single fraction [29]. Thus, in this work, four seed positions in a single catheter were used to deliver a 20 Gy single dose to the planning tumor volume (PTV).…”
Section: Plos Onementioning
confidence: 99%